Pengaruh Faktor Sosial dan Psikografis terhadap Keputusan Mahasiswa Melakukan Registrasi Akademik (Studi pada Mahasiswa Universitas Dian Nuswantoro Terdaftar dan Aktif Tahun Akademik 2010/2011) - Putri, Primadhany Kartana (Interaksi: Jurnal Ilmu Komunikasi, 2012)
Abstract The present study is to examine the impact of social and psychographic factors on student’s decision in registering academic. The type of study is quantitative descriptive with using positivistic in frame of cognitive learning and information processing theories from Hawskin, Best and Motherbaugh and attribution theory from Fritz Heider. Descriptive factor is used to describe mean score of each factor, and regression is used to analyze hypothesis, which is social and psychographic factors are independent variable and student’s academic registration decision is dependent variable.  The samples are 95 students of Udinus T.A 2010/2011. The propotional random sampling method is used to collect the samples.Finding the research show that the reference group is the indicator of social factor which is stated agree by the students and family indicator is stated less agree. Interest is the indicator of psychographic factor which is stated agree by the students. Regression analysis (T-test) shows partially social and psychographic factors has significant influence on student’s decision in registering academic. Regression analysis (F-test) shows social and psychographic simulation have significant influence on student’s decision in registering academic. Keywords: cognitive learning, information process, attribution, social factor, psychographic factor and student’s decision in registering academic